Expressing and functional analysis of mammalian apoptotic regulators in yeast - Greenwood, M. T. (2010)
The ease by which yeast can be manipulated in conjunction with their similarities to cells of more complex metazoans makes many yeast species, particularly Saccharomyces cerevisae, very attractive models for the study of conserved evolutionary processes that occur in eukaryotes. The ability to functionally express heterologous genes in these cells has allowed the development of countless new and elegant approaches leading to detailed structure-function analysis of numerous mammalian genes. Of these, the most informative have been the studies involving the analysis of regulators that have no direct or obvious sequence orthologue in yeast, including members of the Bcl-2 family of proteins, caspases and tumour suppressors. Here we review the field and provide evidence that these studies have served to further understand mammalian apoptosis.